Lagoa do Quari (São Raimundo Nonato, Piauí): Palaeoenvironment and wetland archaeology in Northeastern Brazil. Issue 6 (11th May 2021) - Parenti, Fabio; Aimola, Giulia; Candelato, Federica; Chaves, Sérgio; Faure, Martine; Ferrari, Sonia; Guérin, Claude; Mengoli, Davide; Natali, Luca; Rioda, Vittorio; Scardia, Giancarlo; Valli, Andrea M. F.
Abstract: Northeastern Brazil has thousands of wetland fossiliferous deposits with megafauna and, in some cases, associated lithic artifacts. The timing of the arrival of humans in South America and the extinction of megafauna is still debated and these sites contribute both to this discussion and to the reconstruction of the Late Pleistocene and Holocene paleoenvironment. Lagoa do Quari, 40 km south of São Raimundo Nonato, Piauí state, is a marsh deposit in the present semiarid caatinga environment, excavated by an interdisciplinary team in 2002–2003. This paper presents the archaeological, palaeontological, geological, chronological, stratigraphical and palynological results and their implications for the Quaternary of northeastern Brazil. The site has a rich megafaunal bonebed at the bottom, dominated by Eremotherium giant sloth remains with poor biodiversity, and a sandy‐silty deposit at the top; two 14 C dates constrain this latter layer to 9, 944–9, 557 and 6, 308–6, 177 cal. years BP and the associated rich lithic industry of quartz and chert shows a technical continuity throughout the Holocene in the region. Palynology describes an open landscape with periodic wet phases, which could explain the richness of the archaeological occurrences in Holocenic Brazilian prehistory. This study offers a model of interdisciplinary enquiry into the paleoenvironment and prehistory of lowland South America. Abstract :